Perkembangan Permukiman di Sekitar Lingkungan Kampus Undip Tembalang - Hapsari, Meifinta Dwi; Pradoto, Wisnu (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Phenomena that occur in Indonesia, is the existence of a education facilities like university in rural areas, one of which occurred in Semarang, that is placed Diponegoro University in Tembalang (the upper region of Semarang). The existence of Undip in this suburb as a form of the development of the city that was equitable development with the spread of urban facilities. This research uses a quantitative approach. The Results of this research that is the existence of Undip influenced the development of settlement in Tembalang Village and Pedalangan Village. For the whole region in Tembalang Village is affected by the exsitence of the Undip. For the development of settlement in Pedalangan Village is divided into two parts, that is the development of the northern part of physical and non- physical areas affected by the existence of educational activities such as the existence of the Undip College, then the existence of Politekkes and other educational activities . Another region Pedalangan Village, the southern region for the development of physical and non-physical are affected by the exsitence of the Perumnas and because of the development of Banyumanik region.